2018
DOI: 10.1002/anie.201808433
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Folding Polymer Film Based on Swelling Metal–Organic Frameworks

Abstract: Herein, we exploit the well-known swelling behaviour of metal-organic frameworks (MOFs) to create a self-folding polymer film. Namely, we show that incorporating crystals of the flexible MOF MIL-88A into a polyvinylidene difluoride (PVDF) matrix affords a polymer composite film that undergoes reversible shape transformations upon exposure to polar solvents and vapours. Since the self-folding properties of this film correlate directly with the swelling properties of the MIL-88A crystals, it selectively bends to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 55 publications
1
62
0
Order By: Relevance
“…Prior to the sorption experiments, samples were degassed inside the chamber under vacuum at 120 °C for 6 h. Folding angles were calculated as previously described. [16] A Bluepoint 4 ECOcure (Hönle UV Technology) UV-Vis highintensity spot lamp without a filter (300 nm to 650 nm), and a PI 450 (Optris) infrared camera (operating temperature range: 0 ºC to 250 °C), were used. Data were obtained using PI Connect software.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to the sorption experiments, samples were degassed inside the chamber under vacuum at 120 °C for 6 h. Folding angles were calculated as previously described. [16] A Bluepoint 4 ECOcure (Hönle UV Technology) UV-Vis highintensity spot lamp without a filter (300 nm to 650 nm), and a PI 450 (Optris) infrared camera (operating temperature range: 0 ºC to 250 °C), were used. Data were obtained using PI Connect software.…”
Section: Methodsmentioning
confidence: 99%
“…These submicrometer-sized MIL-88A crystals (length: 510 ± 125 nm; width: 266 ± 57 nm) were then used to fabricate MIL-88A@PVDF films with a MOF content of 50 wt%, according to a previously reported method ( Figure S5, Supporting Information). [16] FESEM analysis revealed formation of a uniform film (thickness: 81 ± 5 μm) with an isotropic distribution of the MIL-88A crystals over the entire film ( Figure S6, Supporting Information). Note here that, although embedded MIL-88A crystals retain their reversible swelling behavior ( Figure S7 and S8, Supporting Information), their isotropic distribution induces an isotropic strain over the film, due to their expansion/contraction upon solvent adsorption/desorption, which provokes a negligible folding response ( Figure S5c, Supporting Information).…”
Section: -Insert Figure 1-mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other organic solvents, with tendency to the crystallization of MIL-88B-NH 2 . In this work, it has been presented an outstanding STY of 16000 kg•m −3 •d −1 at soft reaction conditions (T = 100 • C, t = 5 min), which exposes the beneficial use of MW-solvothermal assisted reaction for the industrial production of MIL-88B-NH 2 , which has demonstrated efficiency in applications such as photocatalysis, drug delivery and nanomotors [34][35][36][37]. In contrast, MIL-88B-NH 2 particles with better crystallinity were produced in DMF, and should not be discarded as reaction medium only due to its known toxicity and cost compared with the previously mentioned solvents.…”
Section: Discussionmentioning
confidence: 89%
“…Numerous design approaches such as use of molecular building blocks (MBBs) or secondary building units (SBUs) [4][5][6][7][8][9][10] have been combined with the mathematic discipline of topology [11][12][13] to synthesize myriad novel porous structures, 14 including MOFs that exhibit high performance in crucial environmental and industrial applications such as energy/gas storage separation, [15][16][17][18] waste/valuables removal, 19,20 water harvesting [21][22][23][24][25] and smart materials. [26][27][28] Concerted efforts by chemists and materials scientists have given rise to a new subfield of chemistry: reticular chemistry. The dedicated Reticular Chemistry Structure Resource (RCSR) database created in 2008 by O'Keeffe and coworkers now contains roughly 3,000 three-periodic nets (topologies).…”
Section: Introductionmentioning
confidence: 99%